Analisis Pelayanan Pemungutan Pajak Bumi dan Bangunan (PBB ) Pada Badan Pengelolaan Keuangan dan Pendapatan Daerah Kabupaten Padang Lawas Utara - Siti Rahmah Ritonga (Universitas Islam Negeri Sumatera Utara, 2021)
The objectives of this study are: 1. Determine and describe tax collection services at the Regional Finance and Revenue Management Agency Office of North Padang Lawas Regency. 2. Identify and describe the inhibiting factors in the implementation of land and building tax (PBB) collection services at the Office of the Regional Finance and Revenue Management Agency of North Padang Lawas Regency. This research is a descriptive study with a qualitative approach obtained from observation and in-depth interviews. The research location is in the Office of the Regional Financial and Revenue Management Agency of North Padang Lawas Regency. Informants from employees at BPKPD in the Rural and Urban Land and Building Tax (PBB-P2) section. In this study, the Regional Finance and Revenue Management Agency of North Padang Lawas Regency is the service provider while the community is the recipient of the Property Tax Collection service. Sources of data include primary data and secondary data. Data collection is carried out through observation, interviews, and documentation. Data analysis was carried out using qualitative descriptive analysis techniques illustrating an approach that illustrates that tax collection services at BPKPD PALUTA have been achieved in accordance with the needs of the community's expectations as taxpayers, and there are still obstacles in Tax Collection Services at the Financial and Regional Revenue Management Agency of North Padang Lawas Regency.